FORCED DEGRADATION STUDIES AND ASSESSMENT OF DEGRADATION PRODUCTS OF IMEGLIMIN HYDROCHLORIDE USING LC-ESI/APCI-MS - Talati, A.S.; Dave, H. N. (Rasāyan journal of chemistry, 2024)
Forced degradation subjects drug substances to stress conditions, producing degradation products that are crucial for evaluating stability under accelerated conditions. Imeglimin hydrochloride is a commonly prescribed medicine for managing type 2 diabetes mellitus. This study details the forced degradation experiments and LC-MS analysis of degraded products of Imeglimin Hydrochloride under various stress conditions, offering insights into its stability and providing information on fragmentation pathways and major degradation products. The optimized mobile phase for the LC-MS method was composed of 10 mM ammonium format buffer (pH 3): methanol with a ratio of 75:25 v/v, obtained on an Xtimate C-18 column (flow rate of 0.8 ml/min), with 234 nm as the specific detection wavelength for Imeglimin Hydrochloride. The drug was subjected to stress conditions including photolysis, hydrolysis, thermal, and oxidative stress conditions. After various stress conditions were applied, the complete stability pathways and effects of these stress conditions were examined. Imeglimin hydrochloride underwent degradation when exposed to oxidative conditions at room temperature and basic conditions at elevated temperatures. However, specific degradation products were not found under acidic, thermal, and photolytic stress conditions. By comparing predicted and observed fragmentation patterns and identifying base peaks, LC-MS analysis of Imeglimin Hydrochloride revealed two new degradation products, DP1 (m/z 160.2) and DP2 (m/z 118.0) under oxidative and basic stress conditions, respectively. The developed method was validated as per the guidelines of analytical method validation.